HUBUNGAN PENGETAHUAN KEPALA KELUARGA DENGAN UPAYA PENCEGAHAN TB PARU DI WILAYAH KERJA PUSKESMAS BAROS KOTA SUKABUMI - Sopiyudin, Moh; Danismaya, Irawan; Basri, Burhanudin (Lafadz Jaya Publisher, 2023)
Tuberculosis (TB) is an infectious disease that is a major cause of health problems, one of the 10 highest causes of death in the world and the leading cause of death from a single infectious agent (ranking above HIV/AIDS). Lack of family knowledge about pulmonary tuberculosis can lead to a lack of awareness of the consequences that can be caused by tuberculosis, making people's knowledge and understanding of checking phlegm as an effort to prevent tuberculosis still lacking with the alibi being that they are embarrassed and worried about being diagnosed with pulmonary tuberculosis. The method used in this research is the analytical descriptive method with a cross-sectional approach. The number of samples in this study was 50 respondents. Based on the results of statistical tests with chi-square, the resulting P value is 0.001 < 0.05. It can be concluded that there is a relationship between the knowledge of the head of the family and efforts to prevent pulmonary TB.